Experimental Study on Structural Form and Excavation Model of Urban Metro Cross Transfer Station with Super Large Cross Section and Shallow Excavation - Zhi Lin; Xiang Chen; Hongyun Yang; Chongguo Cheng; Huasong Wang; Changjiang Yang; Genqiao Zhu (Advances in Civil Engineering)
The construction of urban underground cross-interchange transfer subway stations often encounters the difficulties of shallow-buried, different surrounding rock, large spans and heights, congested road traffic, and surrounding buildings sensitive to the construction sequence. Therefore, there is a need for an underground project that controls the stability of underground space and ground subsidence. Based on the construction difficulties of a certain station (the maximum excavation area over 760 m2), this paper conducts a comprehensive selection design of the structure, construction mechanics response, and control technology of this type of interchange station structure and construction excavation. First of all, based on the design experience of large-scale underground transfer transportation engineering and taking full consideration of the stratum conditions, an “arch-wall” cross transfer structure method is proposed. The refined numerical analysis shows that the structure can fully utilize the stratum conditions to reduce the ground surface settlement. Then, in view of the stability of surrounding rock during the construction of a large section, based on the traditional large section excavation method, a construction method of “cross rock beam + heading method” was proposed. In order to verify the effect of the construction method, the three-dimensional detailed numerical model was used to simulate the construction conditions, and the mechanical response characteristics and displacement changes of surrounding rock under each excavation step are explored. Simultaneous interpreting with the traditional large section excavation method, the results show that the new method has advantages in controlling the stability of the surrounding rock. Meanwhile, in order to ensure the safe construction of the project, the self-developed multifunctional engineering test system for traffic tunnels is used to carry out a large-scale physical model experiment to simulate the entire process of the “arch-wall” cross transfer structure construction response characteristics. By analyzing the data of measuring points, the results show that the structure form and the excavation method cause the ground surface settlement, stress, and structural forces meet the requirements for safe construction. Finally, the station can be safely constructed under the new structure form and construction method. Therefore, the structure form and method proposed in this paper can be adapted to the large-scale underground structure under construction in complex environments.